2018
DOI: 10.1111/pai.12858
|View full text |Cite
|
Sign up to set email alerts
|

Reduced CDHR3 expression in children wheezing with rhinovirus

Abstract: Preschool children with RV-induced wheezing were shown to have reduced CDHR3 mRNA levels, which might result in an increased permeability of the epithelial layers of the airways and thereby an increased vulnerability. Thus, measuring CDHR3 mRNA levels might help to identify a more severe phenotype of wheezing preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…This extends a growing body of data implicating the rs6967330 variant in the risk of asthma exacerbations/hospitalization and related traits, including early-life bronchiolitis, earlyonset asthma, and chronic rhinosinusitis. [16][17][18][19]29 Monitoring of gene and protein expression throughout AEC differentiation indicated robust CDHR3 expression before the appearance of cilia. Our finding of CDHR3 localization near the basal bodies in ciliating and mature ciliated cells raised the possibility of its involvement in ciliogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extends a growing body of data implicating the rs6967330 variant in the risk of asthma exacerbations/hospitalization and related traits, including early-life bronchiolitis, earlyonset asthma, and chronic rhinosinusitis. [16][17][18][19]29 Monitoring of gene and protein expression throughout AEC differentiation indicated robust CDHR3 expression before the appearance of cilia. Our finding of CDHR3 localization near the basal bodies in ciliating and mature ciliated cells raised the possibility of its involvement in ciliogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic studies have now associated the rs6967330 SNP with risk of asthma-related illnesses, including in Danish and Japanese patient cohorts. [16][17][18][19] Despite these findings, many questions remain, including (1) whether lung cells other than ciliated cells express CDHR3; (2) whether, as a cadherin-like protein, CDHR3 plays a role in cell adhesion or other ciliated cell functions; (3) whether perturbation of CDHR3 expression in human airway epithelial cells (AECs) modulates HRV-C infection levels; (4) whether the rs6967330 variant of CDHR3 modifies HRV-C infection in AECs; and (5) whether rs6967330 or other cis-variants function as CDHR3 expression quantitative trait loci (eQTLs) and modify risk for childhood asthma exacerbations. Here we use CDHR3 CRISPR-Cas9-edited and CDHR3 risk genotype-specific primary AECs for functional experiments, as well as a comprehensive CDHR3 nasal airway epithelial eQTL analysis and genetic association analysis for CDHR3 functional variants with childhood asthma exacerbations, to answer these questions.…”
Section: Abstract: Airway Epithelium Crispr Rhinovirus Expressionmentioning
confidence: 99%
“…MicroRNA expression is altered in nasal secretions during rhinovirus infection, and in particular increases in hsa-miR-155 may lead to upregulation of genes implicated in the host immune response such as IL8, DPP7 , and SOCS1 (46). Rhinovirus-induced wheezing is also associated with reduced CDHR3 expression in children, which may lead to increased permeability and dysfunction of the airway epithelium (47)—and thus increased susceptibility to infection and immune dysregulation. Another study using cultured primary nasal epithelial cells from children with and without asthma showed that rhinovirus infection affects both DNA methylation and gene expression in children with asthma compared with controls.…”
Section: Studies Of Gene Expression and Asthmamentioning
confidence: 99%
“…In this context, Calu‐3 cell lines and freshly isolated primary nasal epithelial cells had different responses to the exogenous stimuli Staphylococcus aureus enterotoxin B (SEB) and house dust mites (HDM) . The transmembrane protein cadherin‐related family member 3 (CDHR3) was downregulated in peripheral blood leukocytes from children with rhinovirus‐induced wheezing during the acute phase of bronchial obstruction but returned to healthy levels at the follow‐up visit 2‐3 months later, irrespective of the rhinovirus species . It was proposed that the reduced CDHR3 mRNA levels lead to an increase in the permeability of the airway epithelial barrier, increasing susceptibility to allergic diseases.…”
Section: Novel Highlights On Mechanisms Of Allergic Diseasementioning
confidence: 99%